PENGARUH MODEL PEMBELAJARAN JURISPRUDENTIAL INQUIRY TERHADAP CIVIC DISPOSITION PADA SISWA KELAS VII D SMP NEGERI 1 BRINGIN KABUPATEN SEMARANG TAHUN AJARAN 2012/ 2013 - Purnamasari, Nur Anif; Al-Rasyid, Machmud; Suryono, Hassan (Prodi PPKn FKIP UNS, 2017)
This research aboutinfluence Jurisprudential Inquiry model of teaching to civic disposition in students VII D class of SMP Negeri 1 Bringin Kabupaten Semarang Year Of 2012/ 2013. The population of research was all VII students of SMP Negeri 1 Bringin Kabupaten Semarang year of 2012/ 2013, consisting of 160 students. The sample consisted of 72 students taken using a simple random sampling technique. Data collection techniques by using a questionnaire. Test conditions used are normality test, independent, and a linearity test. Phase calculations used in the data analysis is influence the calculation of the amount of the contribution, and the last is the calculation of a simple regression analysis. The conclusion of this research is that there is the influence of Jurisprudential Inquiry model of teaching to civic disposition in students VII D class of SMP Negeri 1 Bringin Kabupaten Semarang Year Of 2012/ 2013.It can be seen from the regression equation obtained is = 30,347 + 0,717X. The contribution of the effect of variable X on Y is equal to 45,74%. Kata Kunci :Model Pembelajaran Jurisprudential Inquiry, Civic Disposition